Pemanfaatan Media Sosial Sebagai Media Pembelajaran - Musyirah Rahman; Ifah Nursyabilah; Peni Astuti; Muh. Irfan Syam; Sam’un Mukramin; Wa Ode Ingra Kurnawati (Journal on Education, 2023)
The development of social media makes performance faster, precise, accurate so as to increase the resulting productivity. The social media that are often used at this time are WhatsApp, Youtube, Facebook, Twitter, Instagram, and other social media. One of the current users of social media is students, because by using social media students can easily communicate near and long distances without having to meet or face to face. Social media for students is important not only as a place to get information but also can improve critical thinking, and can develop skills and creativity in terms of work.This study aims to determine the use of social media for learning media. This study uses a data analysis method that focuses on library research or library research, namely through reading, studying, and examining books and written sources that are closely related to the research problem. Utilization of social media in learning media can further improve the quality of learning if it is used as much as possible. But that does not mean that social media has a negative impact when its use is not controlled and the information is not filtered, errors can occur in the learning process.